Mitologi, Kosmologi dan Religi Orang Sentani - Peyon, Ibrahim (Universitas Cenderawasih, 2022)
This article describes the culture of the Sentani people who inhabit the area around of Sentani Lake and its surroundings. This study describes the views of the Sentani people related to the mythological, cosmological and indigenous of religions in their culture. In Sentani culture, the world consists of three levers, the world in the ground as a high place for the spirits of the dead, the world on the earth's surface where humans live, and the world above the sky is occupied by the good and evil spirits. The world on the surface of the earth is divided into the world of human life, and the world of spirits, where spirits, gods and supernatural are inhabited starting from within the individual, in houses, villages to mountains, lakes, rivers, forests, rocks and seas. All spirits, gods and supernatural are connected through certain rites, symbols, and material cultural relations. These relations are concretized through art carvings, boats, house ornaments, rituals, body carvings, beads and drums, and others. This study intends to reveal and describe the structure of human cognition related to aspects of mythology, cosmology and public belief. This research is a descriptive type of research with an ethnographic approach that collects data through observation, in-depth interviews, and relevant literature studies.